Niobium oxide films deposited by reactive sputtering: Effect of oxygen flow rate - Fernandes, Silvia L.; Affonço, Lucas J. [UNESP]; Junior, Roberto A. R. [UNESP]; da Silva, José H. D. [UNESP]; Longo, Elson; Graeff, Carlos F. de O. [UNESP] (MyJove, 2019)
Reactive sputtering is a versatile technique used to form compact films with excellent homogeneity. In addition, it allows easy control over deposition parameters such as gas flow rate that results in changes on composition and thus in the film required properties. In this report, reactive sputtering is used to deposit niobium oxide films. A niobium target is used as metal source and different oxygen flow rates to deposit niobium oxide films. The oxygen flow rate was changed from 3 to 10 sccm. The films deposited under low oxygen flow rates show higher electrical conductivity and provide better perovskite solar cells when used as electron transport layer.
Keywords: Chemistry; Compact films; Conductivity; Electron transport layer; Issue 151; Niobium oxide film; Perovskite solar cell; Reactive sputtering